PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. KISEL GROUP REGIONAL BALI NUSRA - Sudiyani, Ni Nyoman; Sawitri, Ni Putu Yuliana Ria (Fakultas Ekonomi Universitas Warmadewa, 2024)
This research was carried out in an effort to prove the effect of Job Satisfaction and Job Stress on Employee Performance at PT. Kisel Group Regional Bali Nusra. The population of this research are all employees at PT. Kisel Group Regional Bali Nusra is 50 people. Determination of the sample using the total sampling method with a sample of 50 people. Data analysis techniques used are multiple linear regression analysis, analysis of determination, partial significance test (t-test), and simultaneous significance test (F-test). The results of the analysis provide information that partially job satisfaction and job stress have a positive and significant effect on employee job satisfaction at PT. Kisel Group Regional Bali Nusra. Simultaneously job satisfaction and job stress have a positive and significant effect on employee performance at PT. Kisel Group Regional Bali Nusra. The conclusions from the results of this research include: Job satisfaction partially has a positive and significant effect on employee performance at PT. Kisel Group Regional Bali Nusra, Work Stress partially negative and significant effect on employee performance at PT. Kisel Group Regional Bali Nusra, and job satisfaction and job stress simultaneously have a positive and significant effect on employee job satisfaction at PT. Kisel Group Regional Bali Nusra.